2013
DOI: 10.3390/molecules19010102
|View full text |Cite
|
Sign up to set email alerts
|

1H-2,3-Dihydroperimidine Derivatives: A New Class of Potent Protein Tyrosine Phosphatase 1B Inhibitors

Abstract: A series of 1H-2,3-dihydroperimidine derivatives was designed, synthesized, and evaluated as a new class of inhibitors of protein tyrosine phosphatase 1B (PTP1B) with IC 50 values in the micromolar range. Compounds 46 and 49 showed submicromolar inhibitory activity against PTP1B, and good selectivity (3.48-fold and 2.10-fold respectively) over T-cell protein tyrosine phosphatases (TCPTP). These results have provided novel lead compounds for the design of inhibitors of PTP1B as well as other PTPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…To study the inhibition on the other PTPase family members, SHP1, SHP2, and LAR were prepared and assays were performed according to the procedures described previously (14,18). Briefly, the enzymatic activities of the SHP1, SHP2, and LAR were determined at 30°C by monitoring the dephosphorylation of the substrate 3-omethylfluorescein phosphate (OMFP), and the product was then detected at a 485 nm excitation wavelength and 530 nm emission wavelength by the EnVision multilabel plate reader (Perkin-Elmer Life Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To study the inhibition on the other PTPase family members, SHP1, SHP2, and LAR were prepared and assays were performed according to the procedures described previously (14,18). Briefly, the enzymatic activities of the SHP1, SHP2, and LAR were determined at 30°C by monitoring the dephosphorylation of the substrate 3-omethylfluorescein phosphate (OMFP), and the product was then detected at a 485 nm excitation wavelength and 530 nm emission wavelength by the EnVision multilabel plate reader (Perkin-Elmer Life Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Homogeneous T-cell protein tyrosine phosphatase (TCPTP) inhibitory activities were investigated simultaneously by the same method (14,18). Compound 6f showed 42.2% inhibition at the concentration of 20 lg/mL (31.35 lM), and the result indicated that compound 6f had greater selectivity for PTP1B than for TCPTP.…”
Section: Selectivity Against Other Ptpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is worth noting that PTPs share a high degree of structural conservation in the active site, especially for T-cell protein tyrosine phosphatase (TCPTP), which has a sequence identity of about 74% in the catalytic domains with PTP1B [9]. There is always a challenge for the potent PTP1B inhibitors to keep good selectivity over TCPTP in the same time [10].…”
Section: Introductionmentioning
confidence: 99%